2018
DOI: 10.1111/nmo.13493
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin augments TNBS‐induced colitis through enteric neuronal V1a receptor‐mediated COX‐2‐dependent prostaglandin release from mast cells in mice

Abstract: Background Inflammatory bowel disease (IBD) is a functional disorder with chronic and relapsing clinical features. Vasopressin (VP) is a hormone responsible for water and stress homeostasis and also regulates gastrointestinal inflammation and motility. We explored whether VP was related to IBD pathogenesis and its possible pathway. Methods Colitis was induced by 2,4,6‐trinitrobenzenesulfonic acid (TNBS) in mice. The disease activity and colonic damage were evaluated through a scoring system. Locations of the V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…Low concentrations of AVP caused muscle contraction and stimulated myogenic contractions. This was independent of neuronal activity or mast cell functions (stimulated by AVP activating enteric neurons in mice with 2,4,6‐trinitrobenzenesulfonic acid [TNBS]‐induced colitis; Dou et al, 2019 ), and AVP did not modulate cholinergically mediated contractions. In proximal stomach, the AVP‐induced increase in tone was maintained and appeared unrelated to increases in spontaneous contractions.…”
Section: Discussionmentioning
confidence: 97%
“…Low concentrations of AVP caused muscle contraction and stimulated myogenic contractions. This was independent of neuronal activity or mast cell functions (stimulated by AVP activating enteric neurons in mice with 2,4,6‐trinitrobenzenesulfonic acid [TNBS]‐induced colitis; Dou et al, 2019 ), and AVP did not modulate cholinergically mediated contractions. In proximal stomach, the AVP‐induced increase in tone was maintained and appeared unrelated to increases in spontaneous contractions.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the peripheral role of V 1A R in the inflammatory process of inflammatory bowel disease (IBD) mediated by prostaglandin release was recently reported . In that report, V 1A R was shown to promote COX-2-dependent prostaglandin release from mucosal mast cells in 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice, which was attenuated by conivaptan (a V 1A R antagonist).…”
Section: Resultsmentioning
confidence: 76%
“…58 Similarly, the peripheral role of V 1A R in the inflammatory process of inflammatory bowel disease (IBD) mediated by prostaglandin release was recently reported. 59 In that report, V 1A R was shown to promote COX-2-dependent prostaglandin release from mucosal mast cells in 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis in mice, which was attenuated by conivaptan (a V 1A R antagonist). Additionally, impaired renal water excretion, abnormal renal hemodynamics, and high AVP levels in a mouse model of CCl 4 -induced liver cirrhosis have been reported by Linas et al 60 Similarly, a recent study found upregulated V 1 R expression in the hepatocytes of an ischemia−reperfusion injury mouse model and highlighted the importance of the hepatocyte V 1 R/Wnt/β-catenin/ FoxO3a/Akt pathway in hepatoprotection.…”
Section: Resultsmentioning
confidence: 98%
“…Treatment of myenteric ganglia from the guinea pig colon or ileum with PGE 2 led to prolonged depolarization of enteric neurons with enhanced spike discharge together with an increased neuronal excitability ( 39 41 ) ( Figure 2 ). More recently, myenteric neuron activity and contraction have been shown to depend on prostaglandin release (COX-2 pathway) from mucosal mast cells in a model of TNBS-induced colitis ( 42 ). Similar findings were observed when submucosal neurons of guinea pig colon were treated with PGD 2 ( 43 ).…”
Section: N-6 Oxylipins Regulate Ensmentioning
confidence: 99%